Nontherapeutic equivalence of a generic product of imipenem-cilastatin is caused more by chemical instability of the active pharmaceutical ingredient (imipenem) than by its substandard amount of cilastatin (2019)
ABSTRACT: The generic product had 30% lower concentration of cilastatin compared with the innovator of imipenem-cilastatin. Regarding the active pharmaceutical ingredient (imipenem), wefound no differences in MIC, MBC, concentration or potency or AUC, confirming equivalence in terms of in vitro activity. However, the generic failed therapeutic equivalence in all three animal models. Its Emax against S. aureus in the thigh model was consistently lower, killing from 0.1 to 7.3 million less microorganisms per gram in 24 hours than the innovator (P = 0.003). Against K. pneumoniae in the lung model, the generic exhibited a conspicuous Eagle effect fitting a Gaussian equation instead of the expected sigmoid curve of the Hill model. In the brain infection model with P. aeruginosa, the generic failed when bacterial growth was >4 log10 CFU/g in 24 hours, but not if it was less than 2.5 log10 CFU/g. These large differences in the PD profile cannot be explained by the lower concentration of cilastatin, and rather suggested a failure attributable to the imipenem constituent of the generic product. Analytical chemistry assays confirmed that, besides having 30% less cilastatin, the generic imipenem was more acidic, less stable, and exhibited four different degradation masses that were absent in the innovator.